The Oxford handbook of singing - Nix, John; Welch, Graham (Graham F.); (David Martin) 1956- Howard, David M. (Oxford handbooks., 2019)
Singing has been a characteristic behaviour of humanity across several millennia. Chorus America (2009) estimated that 42.6 million adults and children regularly sing in one of 270,000 choruses in the US, representing more than 1:5 households. Similarly, recent European-based data suggest that more than 37 million adults take part in group singing. 0'The Oxford Handbook of Singing' is a landmark text on this topic. It is a comprehensive resource for anyone who wishes to know more about the pluralistic nature of singing. In part, the narrative adopts a lifespan approach, pre-cradle to senescence, to illustrate that singing is a commonplace behaviour which is an essential characteristic of our humanity. 0In the overall design of the Handbook, the chapter contents have been clustered into eight main sections, embracing fifty-three chapters by seventy-two authors, drawn from across the world, with each chapter illustrating and illuminating a particular aspect of singing. Offering a multi-disciplinary perspective embracing the arts and humanities, physical, social and clinical sciences, the book will be valuable for a broad audience within those fields.